АУТОНОМИЈА ВОЉЕ И ПРАВО НА САМООДРЕЂЕЊЕ ПАЦИЈЕНТА: ПРАВНЕ ГАРАНЦИЈЕ И БИОЕТИЧКЕ ДИЛЕМЕ - Simonović, Ivana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The tremendous advances in medical technology and health care provide many options for prolonging a terminally ill patient's life, often beyond the point at which he is able to derive value from that life or even live free from pain and suffering. These advances made the dying process longer, and raised many questions, some of them being when it is time to stop the futile treatment and who should decide. The principle of autonomy and patient’s right to self-determination assume a pivotal role in health care and doctor-patient’s relation. They may offer the answer to the previously posed questions: patients should have the right not only to refuse the treatment or to request their discontinuation (which is already an established golden rule of patient’s care), but they also should be given the right to request aid in dying.  Euthanasia and other forms of assisted dying are legal in just few countries. In Serbia these practices are sanctioned as criminal offences. Yet, the Preliminary Draft of the Civil Code of Serbia establishes a new subjective (personal) right - the right to a dignified death (euthanasia), which may be exercised in exceptional circumstances by fulfilling the specifically prescribed humane, psycho-social and medical conditions. Public educated debate is much needed before the legislator makes the final word. Legal scholars are certainly invited to participate in this discussion, but public in general must also be heard.
Keywords: the right to life; the inviolability (sanctity) of life; private autonomy; self-determination; dignity; euthanasia; patients' rights; refusal of medical treatment; palliative care; bio-ethical dilemmas